Effect of Bovatec® and Synovex-S® implants on finishing steer performance - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station, 2011)
Cattle fed Bovatec consumed 18.3% less feed and were 19.4% more efficient in feed conversion than controls, with no effect on gain. Synovex-S implants improved gain by 8.2% with no effect on feed intake and feed efficiency. The effects of Bovatec and Synovex-S were additive.
Keywords: Beef; Implants; Steer; Performance